The Arabidopsis TOR Kinase Specifically Regulates the Expression of Nuclear Genes Coding for Plastidic Ribosomal Proteins and the Phosphorylation of the Cytosolic Ribosomal Protein S6 - Dobrenel, Thomas; Mancera-Martínez, Eder; Forzani, Céline; Azzopardi, Marianne; Davanture, Marlène; Moreau, Manon; Schepetilnikov, Mikhail; Chicher, Johana; Langella, Olivier; Zivy, Michel; Robaglia, Christophe; Ryabova, Lyubov A.; et al. (Frontiers in Plant Science, 2016)
Protein translation is an energy consuming process that has to be fine-tuned at both the cell and organism levels to match the availability of resources. The target of rapamycin kinase (TOR) is a key regulator of a large range of biological processes in response to environmental cues. In this study, we have investigated the effects of TOR inactivation on the expression and regulation of Arabidopsis ribosomal proteins at different levels of analysis, namely from transcriptomic to phosphoproteomic. TOR inactivation resulted in a coordinated down-regulation of the transcription and translation of nuclear-encoded mRNAs coding for plastidic ribosomal proteins, which could explain the chlorotic phenotype of the TOR silenced plants. We have identified in the 5’ untranslated regions (UTRs) of this set of genes a conserved sequence related to the 5’ Terminal OligoPyrimidine (TOP) motif, which is known to confer translational regulation by the TOR kinase in other eukaryotes. Furthermore, the phosphoproteomic analysis of the ribosomal fraction following TOR inactivation revealed a lower phosphorylation of the conserved Ser240 residue in the C-terminal region of the 40S ribosomal protein S6 (RPS6). These results were confirmed by Western blot analysis using an antibody that specifically recognizes phosphorylated Ser240 in RPS6. Finally, this antibody was used to follow TOR activity in plants. Our results thus uncover a multi-level regulation of plant ribosomal genes and proteins by the TOR kinase.